2013
DOI: 10.1590/s1516-18462013005000042
|View full text |Cite
|
Sign up to set email alerts
|

Influência da mídia sobre o olhar pedagógico da gagueira: reflexões iniciais

Abstract: Speech Therapy and audiology (FEAD).Conflict of interest: non-existent components should be well balanced for verbal fluency to be achieved.According to Brandi 3 , fluency is characterized by sequence, duration, speed and rhythm. These four parameters are frequently altered in stuttered speech.Formerly, disfluency was often seen as an error or defect of speech. Today, however, it is no longer regarded thus, since disfluency is known to allow time for the speaker to solve momentary difficulties concerning "what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 11 publications
5
4
0
4
Order By: Relevance
“…As description of the results, the vast majority of educators had seen or knew someone who stutters, which goes against the available literature (7)(8)(9)(10)(11) , demonstrating that stuttering is a known issue, though educators do not know how to deal with these individuals (10) . The data indicated that most respondents believed to be a high prevalence of the disorder in the general population.…”
Section: Discussionmentioning
confidence: 79%
“…As description of the results, the vast majority of educators had seen or knew someone who stutters, which goes against the available literature (7)(8)(9)(10)(11) , demonstrating that stuttering is a known issue, though educators do not know how to deal with these individuals (10) . The data indicated that most respondents believed to be a high prevalence of the disorder in the general population.…”
Section: Discussionmentioning
confidence: 79%
“…Celeste et al (2013), aponta em sua pesquisa que mesmo não recebendo nada do governo, algumas escolas já ofereceram algum tipo de evento com caráter educacional sendo que a grande maioria afirmou que nunca souberam ou participaram de algum tipo de atividade sobre o assunto. Embora não tenha sido encontrado na literatura utilizada, respostas específicas sobre o apoio governamental, sites do governo disponibilizam cartilhas de conteúdo educativo sobre a gagueira, todavia observamos que apenas a existência desse material não tem sido o suficiente para a capacitação dos professores para lidarem com o problema.…”
Section: Resultados E Discussão Gráfico 01 -Você Sabe O Que é Gagueirunclassified
“…Todas as dificuldades escolares e problemas de socialização podem ser amenizados através de ações pedagógicas bem elaboradas e orientadas por um profissional capacitado e com conhecimento específico sobre a gagueira (CELESTE et al 2013). …”
Section: Segundo a Resolução 309 De 01 De Abril De 2005 Do Conselho Funclassified
See 2 more Smart Citations